Quest intro : - Hartmann, Pamela (McGraw-Hill, 2007)
Quest Second Edition parallels and accelerates the process native-speaking students go through when they prepare for success in a variety of academic subjects. Quest helps students get "up to speed" in terms of both academic content and language skills.. The Reading and Writing strand includes three to four distinct units, each focusing on a different area of university study - anthropology, art, biology, business, ecology, economics, history, literature, psychology, and sociology..